1α,25(OH)2D3 Radiosensitizes Cancer Cells by Activating the NADPH/ROS Pathway - Ji, Min-Tao; Nie, Jing; Nie, Xue-Fei; Hu, Wen-Tao; Pei, Hai-Long; Wan, Jian-Mei; Wang, Ai-Qing; Zhou, Guang-Ming; Zhang, Zeng-Li; Chang, Lei; Li, Bing-Yan (Frontiers in Pharmacology, 2020)
The radioresistance of tumors affect the outcome of radiotherapy. Accumulating data suggest that 1α,25(OH)2D3 is a potential anti-oncogenic molecular in various cancers. In the present study, we investigated the radiosensitive effects and underlying mechanisms of 1α,25(OH)2D3 in vitro and in vivo. We found that 1α,25(OH)2D3 enhanced the radiosensitivity of lung cancer and ovarian cancer cells by promoting the NADPH oxidase-ROS-apoptosis axis. Compared to the radiation alone group, the survival fraction and self-renewal capacity of cancer cells treated with combination of 1α,25(OH)2D3 and radiation were decreased. Both apoptosis and ROS were significantly increased in the combination group compared with radiation group. Moreover, N-acetyl-L-cysteine, a scavenger of intracellular ROS, reversed the apoptosis and ROS induced by 1α,25(OH)2D3, indicating that 1α,25(OH)2D3 enhanced the radiosensitivity of cancer cells in vitro by promoting ROS-induced apoptosis. Moreover, our results demonstrated that 1α,25(OH)2D3 promoted ROS level via activating NADPH oxidase complexes, NOX4, p22phox and p47phox. In addition, knockdown of vitamin D receptor (VDR) abolished the radiosensitization of 1α,25(OH)2D3, which confirmed that 1α,25(OH)2D3 radiosensitized tumor cells depend on VDR. Similarly, our study also evidenced that vitamin D3 enhanced the radiosensitivity of cancer cells in vivo and extended the overall survival of mice with tumor. In summary, these results demonstrated that 1α,25(OH)2D3 enhanced the radiosensitivity depend on VDR and activating NADPH oxidase-ROS-apoptosis axis. Our findings suggest that 1α,25(OH)2D3 in combination with radiation enhances lung and ovarian cells radiosensitivity, potentially providing a novel combination therapeutic strategy.